Glacier recession and water resources in Peru’s Cordillera Blanca - Baraer, Michel (2012)
Original abstract: The tropical glaciers of the Cordillera Blanca, Peru, are rapidly retreating, resulting in complex impacts on the hydrology of the upper Río Santa watershed. The effect of this retreat on water resources is evaluated by analyzing historical and recent time series of daily discharge at nine measurement points. Using the Mann-Kendall nonparametric statistical test, the significance of trends in three hydrograph parameters was studied. Results are interpreted using synthetic time series generated from a hydrologic model that calculates hydrographs based on glacier retreat sequences. The results suggest that seven of the nine study watersheds have probably crossed a critical transition point, and now exhibit decreasing dry-season discharge. Our results suggest also that once the glaciers completely melt, annual discharge will be lower than present by 2-30% depending on the watershed. The retreat influence on discharge will be more pronounced during the dry season than at other periods of the year. At La Balsa, which measures discharge from the upper Río Santa, the glacier retreat could lead to a decrease in dry-season average discharge of 30%.